Important role of H2 spillover in asymmetric hydrogenation of quinolines in hybrid systems - Yiqi Ren; Xin Liu; Jiali Liu; Huicong Dai; Maodi Wang; Qihua Yang (Nature Communications)
Abstract The phenomenon of hydrogen spillover usually involved in the hydrogenation reactions over supported metal catalysts has been seldom reported over molecular catalysts. Herein, we report the important role of hydrogen spillover in homogeneous hydrogenation with the asymmetric hydrogenation of quinolines as a model reaction. It is observed that the conversion of quinaldine over TsDPEN-Rh-Cp*-Cl catalyst is sharply increased by 2.1 folds in the presence of Ni/TiO2 and the ee value remained at the same level. The mechanism study shows that Ni/TiO2 is mainly used as H2 dissociation site, TsDPEN-Rh-Cp*-Cl is the active site to control the enantioselectivity of the product, and hydrogen spillover acts as a bridge between the two catalysts in the homogeneous and heterogeneous hybrid system. The hydrogen spillover makes it possible for heterogeneous catalysts and homogeneous organometallic complexes to cooperate, breaking the boundary between homogeneous and heterogeneous catalysis.